Leveraging defense-in-depth through a deception-driven security model for smart university - Marlon A. Naagas; Anazel P. Gamilla; Mary Camille D. Rabang (Bulletin of Electrical Engineering and Informatics, 2026)
Cybersecurity remains one of the biggest challenges to address as the education sector shifts to the smart university concept. The education sector has experienced in recent years a noticeable rise in cyberattacks, revealing limitations in relying solely on traditional defense-in-depth (DID) security strategies. In response, the study implements a deception-driven security model (D-DSM) designed for a campus network environment. The proposed model incorporates decoy resources managed through a centralized deception mechanism to mislead attackers, divert malicious activities away from critical assets, and provide meaningful indicators of attack behavior, resulting in a more effective way to mitigate attacks. Rather than replacing existing defenses, the model complements current security controls by improving the visibility of advanced and lateral attacks while helping reduce false alerts. Adding deception as an active security layer is a useful way to make networks more resilient and helps build smarter, safer, and more sustainable university infrastructures.